2020
DOI: 10.1111/febs.15347
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of a designer protein sheds light on β‐propeller protein evolution

Abstract: b-propeller proteins are common in nature, where they are observed to adopt 4-to 10-fold internal rotational pseudo-symmetry. This size diversity can be explained by the evolutionary process of gene duplication and fusion. In this study, we investigated a distorted b-propeller protein, an apparent intermediate between two symmetries. From this template, we created a perfectly symmetric 9-bladed b-propeller named Cake, using computational design and ancestral sequence reconstruction. The designed repeat sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Alternatively, they may have just retained the closure present in the ancestral motif prior to duplication and fusion. Future experiments using different recently designed proteins, such as Tako8 and Cake9, belonging to different propeller families may shed further light on the matter 29,30 . Nevertheless, the propeller fold may be highly successful because of an intrinsic adaptability that allows individual proteins to adopt different permutations to regulate their flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they may have just retained the closure present in the ancestral motif prior to duplication and fusion. Future experiments using different recently designed proteins, such as Tako8 and Cake9, belonging to different propeller families may shed further light on the matter 29,30 . Nevertheless, the propeller fold may be highly successful because of an intrinsic adaptability that allows individual proteins to adopt different permutations to regulate their flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Some motifs permit multiple symmetries. The Cake sequence for example can both fold into an eight-and nine-bladed propeller depending on the number of repeats expressed [Mylemans et al, 2020a], and the WRAP sequence has also been shown to possess this property [Afanasieva et al, 2019]. Most sequences however will only properly fold in a specific symmetry; Pizza will only adopt a six-bladed propeller, even when seven repeats are tandemly placed in a single polypeptide Voet et al [2014].…”
Section: Discussionmentioning
confidence: 99%
“…[Voet et al, 2015, Shang andNienhaus, 2015] Other Pizza derivatives exhibited catalytic activity [Clarke et al, 2019], bound inorganic metaloxoclusters [Vandebroek et al, 2020], or were joined with α-helices to create protein cages [Vrancken et al, 2020]. As symmetric proteins are highly interesting for the creation of symmetric macromolecular assemblies, the same computational design strategy was subsequently used to make the eight-bladed propeller, Tako8 [Noguchi et al, 2019] and the ninebladed propeller Cake9 [Mylemans et al, 2020a]. The latter can also fold as an eight-bladed propeller when only eight repeats are expressed.…”
mentioning
confidence: 99%
“…Mylemans et al attempted to recreate a symmetric -propeller based on a naturally occurring incomplete propeller domain. By following the RE 3 volutionary protein design approach with a 9-fold symmetric backbone, an idealized sequence was obtained, named Cake [66] . Surprisingly, truncated variants were found to fold as -propellers with either eight or nine blades ( Fig.…”
Section: Globular Symmetrical Proteinsmentioning
confidence: 99%